Successful treatment of an adolescent patient with acute subclavian vein occlusion using the Cleaner thrombectomy device: Subclavian vein DVT in adolescent patient and treatment with the Cleaner device - İştar , Hande and Sevük , Utkan (Journal of Surgery and Medicine, 2022)
Paget-Schroetter Syndrome is a rare condition characterized by the thrombosis of the axillary and/or subclavian vein due to repetitive activity of the upper extremity. This effect results in exertion-induced deep venous thrombosis (DVT) of the upper extremity. In the literature, it has been reported more frequently among the adult population. We aimed to introduce a 15-year-old female patient who suffered an acute DVT of the left upper extremity, and her successful treatment using the Cleaner thrombectomy device.